A qualitative exploration of the barriers and facilitators affecting ethnic minority patient groups when accessing medicine review services: Perspectives of healthcare professionals. (23rd December 2021) - Robinson, Anna; Elarbi, Muna; Todd, Adam; Husband, Andy
Abstract: Introduction: Healthcare inequalities and ethnicity are closely related. Evidence has demonstrated that patients from ethnic minority groups are more likely to report a long‐term illness than their white counterparts; yet, in some cases, minority groups have reported poorer adherence to prescribed medicines and may be less likely to access medicine services. Knowledge of the barriers and facilitators that impact ethnic minority access to medicine services is required to ensure that services are fit for purpose to meet and support the needs of all. Methods: Semistructured interviews with healthcare professionals were conducted between October and December 2020, using telephone and video call‐based software. Perspectives on barriers and facilitators were discussed. Interviews were audio‐recorded and transcribed verbatim. Reflexive thematic analysis enabled the development of themes. QSR NVivo (Version 12) facilitated data management. Ethical approval was obtained from the Newcastle University Faculty of Medical Sciences Ethics Committee. Results: Eighteen healthcare professionals were interviewed across primary, secondary and tertiary care settings; their roles spanned medicine, pharmacy and dentistry. Three themes were developed from the data regarding the perceived barriers and facilitators affecting access to medicine services for ethnic minority patients. These centred around patient expectations of health services; appreciating cultural stigma and acceptance of certain health conditions; and individually addressing communication and language needs. Conclusion: This study provides much‐needed evidence relating to the barriers and facilitators impacting minority ethnic communities when seeking medicine support. The results of this study have important implications for the delivery of person‐centred care. Involving patients and practitioners in coproduction approaches could enable the design and delivery of culturally sensitive and accessible medicine services. Patient or Public Contribution: The Patient and Public Involvement and Engagement (PPIE) group at Newcastle University had extensive input in the design and concept of this study before the research was undertaken. Throughout the work, a patient champion (Harpreet Guraya) had input in the project by ensuring that the study was conducted, and the findings were reported, with cultural sensitivity.